Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.4070/kcj.2016.46.4.522
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between P & QT Dispersions and Presence & Severity of Stable Coronary Artery Disease

Abstract: Background and ObjectivesThe study aimed to evaluate the correlation between electrocardiographic (ECG) parameters and presence and extent of coronary artery disease (CAD) to indicate the usefulness of these parameters as predictors of severity in patients with stable CAD.Subjects and MethodsTwo hundred fifty patients, without a history of any cardiovascular event were included in the study. The ECG parameters were measured manually by a cardiologist before coronary angiography. The patients were allocated int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 26 publications
2
5
0
2
Order By: Relevance
“…Given the systemic nature of atherosclerosis, there is a high prevalence of CAD in the patient population scheduled for PABS. Recent studies have shown that coronary angiography and revascularization as needed prevent postoperative cardiac complications during and after noncardiac surgery [ 8 , 9 ]. In daily practice, it is a common approach for surgeons to monitor patients undergoing PABS for underlying obstructive CAD when they have a history of CAD or signs of ischemia on ECG or echocardiography.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Given the systemic nature of atherosclerosis, there is a high prevalence of CAD in the patient population scheduled for PABS. Recent studies have shown that coronary angiography and revascularization as needed prevent postoperative cardiac complications during and after noncardiac surgery [ 8 , 9 ]. In daily practice, it is a common approach for surgeons to monitor patients undergoing PABS for underlying obstructive CAD when they have a history of CAD or signs of ischemia on ECG or echocardiography.…”
Section: Discussionmentioning
confidence: 99%
“…QTD also indicates heterogeneity of ventricular repolarization. Repolarization impairments caused by ischemia and regional fibrosis due to chronic ischemia may be the reasons for the increased QTD detected in patients with CoAD [ 9 ]. QTD may increase the incidence of sudden death and ventricular tachycardia in various cardiovascular conditions and noncardiac diseases [ 7 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Salah satu pemeriksaan noninvasif yang mudah dilakukan untuk penegakkan diagnosis, penentuan prognosis, dan risiko kardiovaskular PJK adalah pengukuran interval QT (IQT) pada elektrokardiogram (EKG). [7][8][9] Pemanjangan IQT merupakan penanda aritmia ventrikel dan KJM. Perbedaan antara interval QT terpanjang dengan terpendek dikenal sebagai dispersi QT (QTd).…”
Section: Pendahuluanunclassified
“…Perbedaan antara interval QT terpanjang dengan terpendek dikenal sebagai dispersi QT (QTd). [8][9][10][11] Dispersi QT merupakan ukuran heterogenitas repolarisasi miokardial yang mampu memprediksi kejadian aritmia ventrikular yang menjadi penyebab KJM. 4,11,12 Beberapa studi juga menunjukkan pemanjangan QTd yang meningkat pada pasien dengan penyakit jantung koroner.…”
Section: Pendahuluanunclassified